Le protesi nelle fratture del collo femorale - Pantalone, A.; Polidoro, F.; Rea, R.; Salini, V. (Lo Scalpello - Journal, 2019)
HIP PROSTHESIS FOR FEMORAL NECK FRACTURES Intracapsular fractures of the proximal femur account for a major share of fractures in the elderly and result from low energy trauma; in these cases hip replacement arthroplasty is a viable treatment option. A timely and appropriate treatment of hip or proximal femur fracture lead to reduction in the risk of complications associated with prolonged bed rest in older persons. In this regard, the use of different prosthetic hip joints should be considered to achieve the best risk-benefit and cost-effective ratio.